2021
DOI: 10.1101/2021.02.03.429644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of a first-in-class inhibitor of the PRMT5-substrate adaptor interaction

Abstract: PRMT5 and its substrate adaptor proteins (SAPs), pICln and Riok1, are synthetic lethal dependencies in MTAP-deleted cancer cells. SAPs share a conserved PRMT5 binding motif (PBM) which mediates binding to a surface of PRMT5 distal to the catalytic site. This interaction is required for methylation of several PRMT5 substrates, including histone and spliceosome complexes. We screened for small molecule inhibitors of the PRMT5-PBM interaction and validated a compound series which binds to the PRMT5-PBM interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
(1 reference statement)
0
13
0
Order By: Relevance
“…To inhibit PRMT5 signaling in human diseases, one could envision blocking one or both of these steps. In this regard, we recently discovered a covalent inhibitor of the PBM interaction that recapitulates the displacement effects of the PRMT5 ADA mutant (McKinney et al, 2021). Given the effects of perturbing the PBM site on cell growth coupled with previous findings that existing PRMT5 catalytic inhibitors are not selective for MTAP-null cells (Mavrakis et al, 2016), this presently defined site on the PRMT5 methylosome may provide a therapeutic target in CDKN2A/MTAP-deleted tumors.…”
Section: Discussionmentioning
confidence: 96%
“…To inhibit PRMT5 signaling in human diseases, one could envision blocking one or both of these steps. In this regard, we recently discovered a covalent inhibitor of the PBM interaction that recapitulates the displacement effects of the PRMT5 ADA mutant (McKinney et al, 2021). Given the effects of perturbing the PBM site on cell growth coupled with previous findings that existing PRMT5 catalytic inhibitors are not selective for MTAP-null cells (Mavrakis et al, 2016), this presently defined site on the PRMT5 methylosome may provide a therapeutic target in CDKN2A/MTAP-deleted tumors.…”
Section: Discussionmentioning
confidence: 96%
“…However, suitable inhibitors might be able to disrupt the PPI as a novel therapeutic strategy, as was shown by the recent preliminary report of the group of Ianari. [16]…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Previously, cell TE for PRMT5 inhibitors has been demonstrated via imaging-based detection of symmetrically dimethylated nuclear proteins 45,46 as well as in a PRMT5-RIOK1 protein-protein interaction NanoBiT assay in permeabilised cells. 47,48 Recently, studies have shown that NanoBRET assays using bespoke ETP probes are a powerful means to study direct TE in a quantitative fashion 22,49 . While CETSA has been established for PRMT5 previously, 15 a key advantage of the NanoBRET system is its ability to provide a continuous quantitative readout of cellular TE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PRMT5 has a several accessible cysteine residues (C278, C449) which has enabled the development of covalent inhibitors. 48,52 Currently, there is limited data with regard to the global specificity of PRMT inhibitors. We have previously investigated the proteome-wide selectivity of the pan-type I inhibitor MS023.…”
Section: Discussionmentioning
confidence: 99%